Rekayasa Teknologi Fermentasi Limbah Rumput Laut sebagai Probiotik pada Budidaya Intensif Ikan Sistem Akuaponik [Engineering Technology Fermentation Waste Seaweed As Probiotics On The Cultivation Of Intensive Fish Aquaponic System] - Moch. Amin Alamsjah; Harjad Subangkit (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract This research is done by doing a test fermentation technology in order to manufacture enriched media probiotic (probiotic 's) and the identification of the type and number of probiotic bacteria, and nutrient elements absorption of N and P. Results obtained shows that the number of microbes Lactobacillus sp. as probiotic bacteria may increase on media waste Gracilaria sp., Kappaphycus sp., Sargassum sp. and the levels of nitrogen and phosphor is high from fermented waste with media indicating that the fermentation kelp Gracilaria sp. waste provides the best results compared to fermentation waste Kappaphycus sp. and Sargassum sp.